Risk of Epilepsy after Perinatal Stroke - J Gordon Millichap (Pediatric Neurology Briefs)
The prevalence and severity of epilepsy after 6 months of age in 64 children with a history of perinatal stroke were studied by a retrospective review of patients at Riley Hospital for Children, Indianapolis, IN.